Testing for seasonal unit roots in heterogeneous panels (2005)
This paper uses the approach of Im, Pesaran and Shin [Im, K.S., Pesaran, M.H., Shin, Y., 2003. Testing for unit roots in heterogeneous panels. Journal of Economics 115, 53-74.] to propose seasonal unit root tests for dynamic heterogeneous panels. The standardised t-bar and F-bar statistics are simply averages of the HEGY tests across groups. These statistics converge to standard normal variates. © 2004 Elsevier B.V. All rights reserved.